Particle-bound Polycyclic Aromatic Hydrocarbons (pPAHs) in Merida, Mexico - Harry Alvarez-Ospina; Sofia Giordano; Luis A. Ladino; Graciela B. Raga; Joshua I. Muñoz-Salazar; Martha Leyte-Lugo; Daniel Rosas; Giovanni Carabali (Aerosol and Air Quality Research)
Abstract This study focuses on the air quality evaluation of Merida, a medium-size city located in the Yucatan Peninsula with a significant population growth in recent years. Particle-bound Polycyclic Aromatic Hydrocarbons (pPAHs) were quantified with a real time sensor during a six-month period during the dry season (October 2017 to March 2018). The pPAHs diurnal and monthly characteristics, as well as their potential sources were determined. The total pPAHs concentrations ranged from 7 ng m−3 to 170 ng m−3, with an average value of 19 ± 11 ng m−3. A seasonal trend was observed, albeit not complete, indicating that pPAHs concentrations were higher during the colder months (October through January) than in February and March. The diurnal cycle showed a bimodal behavior similar to those found for carbon monoxide (CO), nitrogen oxides (NOx) and black carbon (BC) (estimated from absorption coefficient), indicating that burning of fossil fuels from vehicular traffic is the likely source of the pPAHs emitted in Merida. Moreover, atypical nocturnal values were observed, where the high pPAHs concentration could be associated with the burning of solid waste. The average pPAHs concentration obtained in this study (19 ± 11 ng m−3) were found to be lower than the values measured in two other sites in Mexico City (32 ng m−3 and 50 ng m−3), Boston (29 ng m−3), Los Angeles (88.3 ng m−3) and Quito (220 ng m−3).